2022
DOI: 10.2337/db21-0801
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-29 Ameliorates Fibro-Inflammation and Insulin Resistance in HIF1α-Deficient Obese Adipose Tissue by Inhibiting Endotrophin Generation

Abstract: Dysregulation of extracellular matrix proteins in obese adipose tissue (AT) induces systemic insulin resistance. The metabolic roles of type VI collagen and its cleavage peptide endotrophin in obese AT are well established. However, the mechanisms regulating endotrophin generation remain elusive. Herein, we identified that several endotrophin-containing peptides (pre-endotrophins) were generated from the COL6A3 chain in a stepwise manner for the efficient production of mature endotrophin, partly through the ac… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 52 publications
2
5
0
Order By: Relevance
“…We found elevated levels specifically of MMP9 mRNA, MMP9 protein and activity in abundant PPAT. This is consistent with a report that in vitro MMP9 activity, along with MMP2 and MMP16, is key to produce active endotrophin (Jo et al, 2022), which might explain the high levels of this matrikine in abundant PPAT.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…We found elevated levels specifically of MMP9 mRNA, MMP9 protein and activity in abundant PPAT. This is consistent with a report that in vitro MMP9 activity, along with MMP2 and MMP16, is key to produce active endotrophin (Jo et al, 2022), which might explain the high levels of this matrikine in abundant PPAT.…”
Section: Discussionsupporting
confidence: 93%
“…We found elevated levels specifically of MMP9 mRNA, MMP9 protein and activity in abundant PPAT. This is consistent with a report that in vitro MMP9 activity, along with MMP2 and MMP16, is key to produce active endotrophin (Jo et al, 2022), which might explain the high levels of this matrikine in abundant PPAT. At first sight, our findings appear to contradict those of a study that used inducible adipocyte-specific endotrophin overexpression, which found that endotrophin amplifies AT dysfunction in obesity by enhancing fibrosis and inflammation leading, ultimately, to increased insulin resistance (Sun et al, 2014).…”
Section: Discussionsupporting
confidence: 93%
“…Interestingly, endostatin inhibits MMP2 activity [60], suggesting that intact COL18A1 is a marker of healthy aging. Alternatively, in addition to the IGF/IGFBP/IGFALS ternary complex, MMP2 can cleave COL6A3 to generate endotrophin [61], which is associated with onset of obesity-related metabolic disorders [62]. However, MMP2 is more likely to capture intact COL6A3, and cannot characterize its cleavage activity.…”
Section: Discussionmentioning
confidence: 99%
“… Mechanism for how adipose endotrophins are made in obese adipose tissue. The latest findings by Jo et al ( 11 ) are highlighted in red. …”
mentioning
confidence: 96%
“…In this issue of Diabetes , Jo et al ( 11 ) provide new insights that fill the gaps in our understanding of how adipose tissue endotrophin production is increased in obesity. They find that matrix metalloproteinase 2 (MMP2), MMP9, and MMP16 mediate stepwise cleavage of COL6A3 to efficiently produce endotrophin ( Fig.…”
mentioning
confidence: 99%